On magnetic disturbances induced by rotation of coil-type magnetometer driven by seismic waves. Issue 3 (13th May 2021) - Gao, Yongxin; Jiang, Peng; Xu, Yixian; Jiang, Li; Cheng, Chieh-Hung; Zhao, Guoze; Tang, Ji; Chen, Xiaobin; Han, Bin; Chong, Jiajun; Yao, Cheng
SUMMARY: Rotation of coil-type magnetometers caused by seismic waves can change the magnetic flux of the earth's magnetic field through the coils and thereby give rise to rotation-induced magnetic fields (RIMFs), which have contribution to so-called coseismic magnetic disturbances during earthquake events. In this study, we present a method to numerically calculate the rotational motion and RIMFs excited by a seismic source in a horizontally layered model. Like computing synthetic seismograms, this method allows calculating the full response of magnetic disturbances during an earthquake event. Numerical examples are conducted to investigate characters of the magnetic fields under excitation of different kinds of sources. The results show that the P -SV-mode waves mainly contribute to radial and vertical magnetic disturbances, while the SH-mode waves dominate tangential magnetic disturbances. We also apply this method to the 2017 Jiuzhaigou earthquake. The synthetic magnetic signals explain well the observed data, suggesting that the coseismic magnetic fields observed during this earthquake are mainly caused by the rotation of the magnetometers.